UMP rewarded staff and community for quality service and exemplary work - UMP, PNC (2019)
A total of 149 University Malaysia Pahang (UMP) staff received the Excellent Service Award while 20 were recipients of the Excellent Performance Prize, which marked the university’s recognition of their quality services.